Software quality : the future of systems- and software development : 8th International Conference, SWQD 2016, Vienna, Austria, January 18-21, 2016, Proceedings /: the future of systems- and software development : 8th International Conference, SWQD 2016, Vienna, Austria, January 18-21, 2016, Proceedings. ([2015]) - Unknown
No abstract available